2018
DOI: 10.1080/21645515.2018.1442996
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to the hepatitis B antigen in the RTS,S/AS01 malaria vaccine, and co-administration with pneumococcal conjugate and rotavirus vaccines in African children: A randomized controlled trial

Abstract: The RTS,S/AS01 malaria vaccine (Mosquirix) reduces the incidence of Plasmodium falciparum malaria and is intended for routine administration to infants in Sub-Saharan Africa. We evaluated the immunogenicity and safety of 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV; Synflorix) and human rotavirus vaccine (HRV; Rotarix) when co-administered with RTS,S/AS01 (www.clinicaltrials.gov NCT01345240) in African infants. 705 healthy infants aged 8–12 weeks were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Another advantage of using HBsAg as vaccine carrier is the potential value of antibodies against such a carrier: once proven that they do not impact the antigen-specific response, these antibodies could be beneficial against HBV infection. For example, the RTS,S/AS01 vaccine induces in human HBsAg-specific antibody response non-inferior to EngerixB R vaccination (39); however, RTS,S has only 20% of HBsAg genetically fused to the CSP-based antigen, leaving the VLP well-exposed to the immune system. Differently, a new vaccine candidate R21, composed solely by HBsAg genetically fused to a C-terminal portion of CSP, does not induce anti-HBsAg antibodies in mice; this is related to inaccessibility of the HBsAg, masked by the antigen (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of using HBsAg as vaccine carrier is the potential value of antibodies against such a carrier: once proven that they do not impact the antigen-specific response, these antibodies could be beneficial against HBV infection. For example, the RTS,S/AS01 vaccine induces in human HBsAg-specific antibody response non-inferior to EngerixB R vaccination (39); however, RTS,S has only 20% of HBsAg genetically fused to the CSP-based antigen, leaving the VLP well-exposed to the immune system. Differently, a new vaccine candidate R21, composed solely by HBsAg genetically fused to a C-terminal portion of CSP, does not induce anti-HBsAg antibodies in mice; this is related to inaccessibility of the HBsAg, masked by the antigen (40).…”
Section: Discussionmentioning
confidence: 99%
“…Greater efficacy might be achieved by modification of RTS,S or developing new vaccines [10]. Considering RTS,S has been subject to extensive clinical testing and can be safely co-administered with other vaccines as part of standard childhood immunisation programs [3,[11][12][13][14], working towards improving RTS,S is an attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2016, the World Health Organization (WHO) recommended pilot implementation of the vaccine in children as of 5 months of age in 3 to 5 moderate-to-high malaria transmission settings in Sub-Saharan Africa. 7 Primary study results, published in Valéa et al 8 support the indication of the RTS,S/AS01 E vaccine for immunization of infants against hepatitis B in settings where prevention of P. falciparum malaria is also being sought. These results demonstrated that RTS,S/AS01 E was non-inferior to a licensed HepB vaccine in terms of anti-HBs seroprotection rates at one month post-primary vaccination.…”
Section: Introductionmentioning
confidence: 90%
“…Details about the coadministered vaccines can be found in the Table 1. Data for participants receiving the different RTS,S/AS01 E (RTS,S groups) or HepB (control groups) primary vaccination regimens (both co-administered in various combinations with different study vaccines), 8 were pooled in RTS,S groups and Table 1. Demographic characteristics per primary vaccination with RTS,S/AS01 E or HepB and co-administered vaccines (ATP cohort for immunogenicity -FU2).…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation